Comparing Moralities in the Abrahamic and Indic Religions Using Cognitive Science: Kindness, Peace, and Love versus Justice, Violence, and Hate - Nakissa, Aria (Religions, 2023)
Recent cognitive science research indicates that humans possess numerous biologically rooted religious and moral intuitions. The present article draws on this research to compare forms of religious morality in the Abrahamic traditions (Judaism, Christianity, Islam) and the Indic traditions (Hinduism, Buddhism, Jainism). Special attention is given to moral teachings on kindness, peace, and love, as well as related teachings on justice, violence, and hate. The article considers how moral intuitions shape Abrahamic/Indic moral teachings, which, in turn, impact: (1) Abrahamic/Indic doctrines concerning politics, law, and war; (2) Abrahamic/Indic doctrines concerning individual ethics, and moral behavior proper to monastics and laypersons; and (3) Abrahamic/Indic doctrines concerning theological matters, such as the nature of the universe, souls, and deities.